1999
DOI: 10.1177/004051759906901212
|View full text |Cite
|
Sign up to set email alerts
|

Decoloration of Azo Dyes by Hydrogen Peroxide Catalyzed by Water-Soluble Manganese Porphyrins

Abstract: Water-soluble manganese porphyrins are catalysts for the decoloration of azo dyes by hydrogen peroxide under mild conditions (pH 8.0 and 25°C). The decoloration rate depends on the structure of the manganese porphyrin and the added ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…Although Reactive blue 19 most likely bears a net negative charge at pH 5, hydrophobic interactions with Merpol may be dominant. This may partially explain our results and is supported by Tokuda et al [21] who has shown that both electrostatic and hydrophobic interactions affected decolorization rates by peroxide bleaching agents in the presence of surfactant molecules.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although Reactive blue 19 most likely bears a net negative charge at pH 5, hydrophobic interactions with Merpol may be dominant. This may partially explain our results and is supported by Tokuda et al [21] who has shown that both electrostatic and hydrophobic interactions affected decolorization rates by peroxide bleaching agents in the presence of surfactant molecules.…”
Section: Discussionsupporting
confidence: 88%
“…This is significant since surfactants are common in dye effluents and can affect not only biological decolorization (whether enzymatic or with a fungal culture) but also physical or chemical decolorization processes [21]. The efficiency of the process will most likely diminish with the degree of interaction between the dye and the surfactant and the quantity of the surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, alternative methods for dye treatment have been investigated, including chemical oxidation with reagents such as: ozone, hydrogen peroxide, ozone/UV, hydrogen peroxide/UV and Fenton's reagent [6][7][8][9][10]. Other alternative techniques such as biological treatment [11][12][13], adsorption and precipitation [14][15][16] and reductive treatment [17][18][19] have applied successfully. For all the proposed techniques, great care has to be taken to keep the costs of such processes at reasonable levels and to avoid the formation of byproducts, which cause additional costs for secondary treatment or disposal.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O 2 itself is a moderate oxidizing agent towards most organic substrates. Activation of hydrogen peroxide by transition metal complexes for the oxidation of organic substrates has been extensively studied 30–36. The heterogeneous activation of H 2 O 2 eliminated the addition of soluble catalysts and may offer a great flexibility in terms of reaction rate.…”
Section: Introductionmentioning
confidence: 99%